ASSESSMENT OF GENETIC VARIABILITY AMONG SOYBEAN EXOTIC GENOTYPES FOR ADAPTABILITY AND YIELD - RAZA, H; AHMED, Z; HASSAN, M; SARWAR, S; SALEEM, S; SHAZAD, S; QAMAR, H; ALTAF, M; MALLHI, AR; SABIR, W; AQEEL, M; REHMAN, AU (Biological and Clinical Sciences Research Journal, 2023)
Comprehensive research was performed in the experimental area in Plant Breeding and Genetics situated in the University of Agriculture Faisalabad to estimate the analysis of variance and correlation of the soybean exotic accessions conducting a randomized complete block design comprising four check varieties. All recommended cultural and agronomic practices were followed homogenously for each experimental genotype during the study. The data for various morphological and phonological characters were recorded from sowing to harvesting and was subjected to measure the analysis of variance of amplified block design and analysis of simple correlation. The analysis of variance revealed that accessions were significantly dissimilar with one another parameter except for days to germination. The findings indicated the variation in the experimental population, reporting the scope of improvement in these traits. The breeding material carries the different ranges of characters such as height of plant starting 14 to 57cm, hundred seed weight from 6 to 42g, number of pods in plant from 4 to 42, number of grains per plant from 8 to 96, germination days from 4 to 10, weight of fresh plant ranges 7 to 186g, maturity days 74 to 135, day to flowering from 24 to 54 and weight of seeds per plant was 9 to 89g. SUMTER, 9831, STARR, Maxcy, 9041, Leslie, ada, and Norman were identi9fied as promising genotypes i9n terms of high yield with better adaptability. Results concluded that considering the plant height, number of pods, and number of seeds are the promising traits for the selection standards and to attain soybean yield.